Cognitive-behavioral program to control lower urinary tract symptoms after radical prostatectomy: a randomized clinical trial - Lívia Cristina de Resende Izidoro; Luciana Regina Ferreira da Mata; Cissa Azevedo; Adriano Augusto Peclat de Paula; M. Graça Pereira; Jackelline Evellin Moreira dos Santos; Virginia Visconde Brasil; Lizete Malagoni de Almeida Cavalcante Oliveira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to assess the effectiveness of a cognitive-behavioral program to control lower urinary tract symptoms after radical prostatectomy. Methods: a randomized clinical trial study, with 41 participants randomized into intervention (n=20) and control (n=21), for three months. The intervention group received the cognitive-behavioral program, while the control group received routine guidance from the service. Outcome variables were urinary incontinence intensity and lower urinary tract symptoms, assessed by the Pad-Test and Urinary Incontinence Scale of Radical Prostatectomy and King's Health Questionnaire. Results: at the end of the study, the intervention group had a lower urinary incontinence intensity (p≤0.001), and there were less chances of presenting changes in urinary frequency (p≤0.001), urinary urgency (p≤0.001), nocturia (p=0.005), stress urinary incontinence (p≤0.001) and urge incontinence (p≤0.045). Conclusion: the cognitive-behavioral program was effective in reducing lower urinary tract symptoms after radical prostatectomy. Brazilian Clinical Trial Registry: RBR-3sstqg.